Cold War on a Warming Planet: Climate Policy in a Divided World - Lucas Bretschger (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
The study examines economic growth and climate change when system competition between countries causes drastic changes in their climate policies. The world is divided into two groups of countries: one that implements strict climate policies and another that refrains from doing so due to concerns about the negative economic impacts. A policy tipping point occurs once the economic performance of the proactive group surpasses that of the laggards, prompting the latter to implement comparable climate measures. I find that the impact of policy tipping is significant on emissions but moderate on economic growth. The occurrence of the policy shift depends on policy design and technological progress. In a divided world, subsidies for clean energy research prove more effective than carbon pricing in accelerating global decarbonization because they induce earlier tipping. Achieving the internationally agreed climate targets requires that proactive countries combine ambitious emissions reductions with sustained economic prosperity, an outcome attainable through an efficient mix of taxes and subsidies.
Keywords: Q43; O47; Q56; O41; 330; carbon policy; divided world; economic growth; global carbon emissions; policy tipping